Standard handbook for civil engineers - Merritt, Frederick S.; Loftin, M. Kent; Ricketts, Jonathan T. (McGraw-Hill, 1996)
This text discusses important principles and techniques that are of use to practicing civil engineers. This edition incorporates significant changes in design and construction practices, specifically in design specifications for structural materials, buildings and bridges, environmental and other federal regulations such as Environmental Protection Agency (EPA) and Occupational Safety and Health Agency (OSHA). Up-to-date code changes from such groups as the American Concrete Institute, American Society for Testing and Materials, American Institute of Steel Construction and National Design Specification for Wood Construction are also covered.